The Bacterial Symbionts of Closely Related Hydrothermal Vent Snails With Distinct Geochemical Habitats Show Broad Similarity in Chemoautotrophic Gene Content - Beinart, Roxanne A.; Luo, Chengwei; Konstantinidis, Konstantinos T.; Stewart, Frank J.; Girguis, Peter R. (Frontiers in Microbiology, 2019)
Symbiosis has evolved between a diversity of invertebrate taxa and chemosynthetic bacterial lineages. At the broadest level, these symbioses share primary function: the bacterial symbionts use the energy harnessed from the oxidation of reduced chemicals to power the fixation of inorganic carbon and/or other nutrients, providing the bulk of host nutrition. However, it is unclear to what extent the ecological niche of the host species is influenced by differences in symbiont traits, particularly those involved in chemoautotrophic function and interaction with the geochemical environment. Hydrothermal vents in the Lau Basin (Tonga) are home to four morphologically and physiologically similar snail species from the sister genera Alviniconcha and Ifremeria. Here, we assembled nearly complete genomes from their symbionts to determine whether differences in chemoautotrophic capacity exist among these symbionts that could explain the observed distribution of these snail species into distinct geochemical habitats. Phylogenomic analyses confirmed that the symbionts have evolved from four distinct lineages in the classes γ-proteobacteria or Campylobacteria. The genomes differed with respect to genes related to motility, adhesion, secretion, and amino acid uptake or excretion, though were quite similar in chemoautotrophic function, with all four containing genes for carbon fixation, sulfur and hydrogen oxidation, and oxygen and nitrate respiration. This indicates that differences in the presence or absence of symbiont chemoautotrophic functions does not likely explain the observed geochemical habitat partitioning. Rather, differences in gene expression and regulation, biochemical differences among these chemoautotrophic pathways, and/or differences in host physiology could all influence the observed patterns of habitat partitioning.